2014
DOI: 10.1016/j.ijfoodmicro.2014.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of free-living protozoa and foodborne pathogens on dishcloths: Implications for food safety

Abstract: In the present study, the occurrence of free-living protozoa (FLP) and foodborne bacterial pathogens on dishcloths was investigated. Dishcloths form a potentially important source of cross-contamination with FLP and foodborne pathogens in food-related environments. First various protocols for recovering and quantifying FLP from dishcloths were assessed. The stomacher technique is recommended to recover flagellates and amoebae from dishcloths. Ciliates, however, were more efficiently recovered using centrifugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 93 publications
1
12
0
Order By: Relevance
“…An interesting study with dishcloth showed the presence of various ciliates along with other food borne pathogen including Arcobacter spp. which urge for adopting good hygienic practices while cooking (Chavatte et al 2014). Talay et al (2016) reported that 36% (41/115) of water samples from various sources (66 sewages, 25 rivers, 16 spring waters and 8 drinking waters) were showed positive for Arcobacter spp.…”
Section: Water-borne Transmission and Prevalencesmentioning
confidence: 99%
“…An interesting study with dishcloth showed the presence of various ciliates along with other food borne pathogen including Arcobacter spp. which urge for adopting good hygienic practices while cooking (Chavatte et al 2014). Talay et al (2016) reported that 36% (41/115) of water samples from various sources (66 sewages, 25 rivers, 16 spring waters and 8 drinking waters) were showed positive for Arcobacter spp.…”
Section: Water-borne Transmission and Prevalencesmentioning
confidence: 99%
“…Vermamoeba vermiformis has been recovered globally from various habitats ranging from snow, soil, to dishcloths (Chavatte et al, 2014; Delafont et al, 2018; Scheid, 2019). Vermamoeba vermiformis was detected in unexpected environments such as industrial water, aerosols and composts of composting facilities, and wastewater from textile industry (Scheid, 2019; Scheikl et al, 2014).…”
Section: Epidemiologymentioning
confidence: 99%
“…FIRST described in 1967, Vermamoeba vermiformis (formerly Hartmannella ) are one of the most widespread free‐living amoebae. They have been recovered from springs, contact lens cases, hospital water systems, dish cloths, and even bottled mineral water (Chavatte et al, 2014; Delafont et al, 2018; Niyyati et al, 2013; Scheid et al, 2019). Moreover, V .…”
mentioning
confidence: 99%
“…have been identified in the intestines and feces of animals (poultry, cattle, pigs, sheep, rabbits), in foods derived from these animals, and from food processing environments. Arcobacter has also been isolated from cheese and other dairy products, seafood, vegetables, and used dishcloths (Collado and Figueras 2011;Chavatte et al 2014;Lastovica et al 2014;Giacometti et al 2015). Other sources are wildlife, zoo and pet animals, zooplankton, human blood, and human feces.…”
Section: Habitatmentioning
confidence: 99%